GAMIFICATION AS A COMPONENT OF STRATEGIC HUMAN CAPITAL DEVELOPMENT MANAGEMENT (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The purpose of the article is to characterize such a tool of strategic management as gamification and its ability to increase the efficiency of human capital management in a short time while maintaining the rationality of this management. It was established that modern definitions of strategic management focus on its following aspects: stability of competitive positions, stability of long-term results, correctness of reactions to changes in the external environment. This indicates the need to correlate the strategic management of human capital with the strategic management of the enterprise in such a way that the goals regarding the need for resources to achieve these goals are as comparable as possible. That is, the strategy of human capital development should derive from the general strategy of the company's development.It has been proven that the strategy of human capital development should identify the methods of its management in order to achieve the set goals as quickly and efficiently as possible. The most effective method most often used to convince the team to achieve goals is motivation. However, popular forms of motivation may not work in the long run. That is, it is about the transition from buying employees to forming their loyalty. Effective engagement is not the result of economic benefits, but internal beliefs that result from variables related to organizational culture.The need to introduce such a strategic management tool as gamification into the general strategy of human capital development is well-founded. The task of strategic human capital management is to gather loyal, highly qualified and responsible employees, dedicated and motivated to achieve long-term goals. The answer to these requirements is gamification - a method of influencing human behavior based on the use of game elements. In concept, games are similar to strategy in that they have structure, rules, and goals. Similar to strategic management in an enterprise, in the game we achieve a goal (victory) by completing certain tasks. The high variability of games ensures the ability of employees to adapt to the environment. In today's economy, only flexible organizations are able to quickly implement non-standard orders, and this is facilitated by gamification.
Keywords: human capital development strategy, strategic management, engaged employee, gamification, organizational culture, game elements